Characterisation and localisation of fertilization independent endosperm and enhancer of zeste-like transcripts from oil palm (Elaeis guineensis Jacq.) - Ramachandran, Vasagi (2014)
Various studies have proved the epigenetic changes in plants have important phenotypic consequences and significant implication in plant breeding programme. Polycomb group genes are one of the key players for epigenetic changes in plants. However, there are no reports on polycomb group genes of oil palm which plays important role in epigenetics. As such, this has prompted the studies on characterisation and localisation of polycomb group genes, EgFIE (KF430194) and EgEZ1 (KF430195) in oil palm owing to its important role in sexual reproduction. The full length transcripts of EgFIE and EgEZ1 were isolated and their expression were analysed and further localised in tissues via real time PCR and in situ hybridisation. The methylation levels in CpG island of each genes were detected by using MSRE-PCR and Southern analysis. The oil palm full length EgFIE cDNA is 1527 bp in length and the ORF is encoding for a protein of 370 amino acids. While, the full length of EgEZ1 transcript is 3200 bp in length with ORF region of 2,757 bp. The expression profile of EgFIE transcript showed that male flower expressed the highest and EgEZ1 transcripts were detected highest in female flower compared to other vegetative and sexual reproductive tissues tested. While for in vitro tissue culture materials, cell suspension culture showed the highest expression of EgFIE and EgEZ1 transcripts among the tissues tested. In the case of different developmental stages of fruits, both clonal Tenera and non-clonal Tenera fruits at 5 WAA showed the highest expression among the tissues tested for both transcripts. The in situ hybridisation analysis showed that the expression of EgFIE and EgEZ1 transcripts were localised in ovary, stigma and stylar canal region of early development stage of fruit and inflorescences. Based on the expression and localisation studies, EgFIE and EgEZ1 genes play important roles in the oil palm inflorescences and fruits development. Both of these genes might have broad functions in oil palm tree development as their expression was detected in a wide range of tissues. The expression of EgFIE and EgEZ1 genes in in vitro tissue culture materials suggest the role of polycomb group complexes as key regulators of dedifferentiation and differentiation pathways in cell culture. On the other hand,methylation analysis showed the HpaII site of EgFIE CpG island region is methylated in clonal 1 DBA and 1 DAA fruits. However, methylation analysis of EgEZ1 CpG island was a failure. In future, more analyses needed on inflorescences,early stages of developing fruit and cell suspension culture to elucidate their roles. Besides that, more advance tools such as bisulphite sequencing and methylated DNA immunoprecipitation can be employed for methylation analysis.